Codice, immagine e paratesto nel ms. Venezia, Biblioteca Nazionale Marciana, It. VI 81 (5795) (Carte Romanze, 2019)
This paper aims to study the ms. Venezia, Biblioteca Nazionale Marciana, It. VI 81 (5795) from a codicological, iconographic and paratextual point of view.
Keywords: material philology; Fiorita d'Italia; Histoire ancienne jusqu'à César; Historia destructionis Troiae; iconography